👤

(x+1)(x-1)(x la a doua +1)(x la a patra+1)
URGENT!


Răspuns :

(x²-1)(x²+1)(x la a patra +1)
(x la a patra -1)(xla a patra +1)⇒X la a opta -1
  ([tex] x^{2} [/tex] -x + x - 1) ( [tex] x^{6} [/tex] + [tex] x^{2} [/tex] + [tex] x^{4} [/tex] +1) =
   = ([tex] x^{2} [/tex] - 1) (tex] x^{6} [/tex] + [tex] x^{2} [/tex] + [tex] x^{4} [/tex] +1) =
= ( [tex] x^{8} [/tex] + [tex] x^{4} [/tex] + [tex] x^{6} [/tex] + [tex] x^{2} [/tex] - [tex] x^{6} [/tex]-[tex] x^{2} [/tex]-[tex] x^{4} [/tex] - 1)=
= [tex] x^{8} [/tex] - 1